Experimental and numerical investigation on a new FSW based metal to composite joining technique. (August 2018) - Baffari, Dario; Buffa, Gianluca; Campanella, Davide; Lo Valvo, Ernesto; Fratini, Livan
Abstract: In the last decades, different techniques were proposed to join aluminum sheets with composites materials. Each of them has advantages and weak points over the others and new techniques and patents are continuously developed to overcome these difficulties. In this paper an experimental and numerical investigation on a new Friction Stir Welding based approach to mechanically join AA6082-T6 to self-reinforced polypropylene is presented. The aluminum sheet is pre-holed along both the sides of the weld line and a pinless tool generates the heat and pressure needed to prompt back-extrusion of the composite. New experimental fixtures and hole designs were investigated in order to enhance the mechanical resistance of the joints and a numerical model was set up to study the process mechanics.